(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present work is based on study of three common freshwater snail species containing parasites. Snails collected were of three species i.e. Indoplanorbis exustus, Lymnaea accuminata and Bellamya bengalenisis. Snails were examined for cercairiae by natural shedding. The present study was focused on two types of cercaria i.e. Xiphidocercaria and Echinostome cercaria.